Auction Procedures for Collateral Goods Owned by Pegadaian Customers (Case Study at Pt Pegadaian (Persero) Branch Mengwi) - I Dewa Putu Andre Wiratama; I Nyoman Putu Budiartha; Nengah Renaya (Journal Equity of Law and Governance, 2023)
The implementation of a sustainable economy will require a lot of funds, and credit institutions such as PT. Pegadaian (Persero) Mengwi Branch can provide a lot of these funds. This institution mainly conducts credit based on mortgage law, which makes it easier for borrowers without creating new problems for them after they provide loans. The problem: What is the procedure for carrying out an auction for collateral at PT. Pegadaian (Persero) Mengwi Branch? And what is the responsibility of PT. Pegadaian (persero) Mengwi Branch for loss or damage to collateral? This study uses empirical research methods. The results of this study indicate that the discussion of PT. Pegadaian (persero) Mengwi Branch gives absolute rights to customers in the event of an auction for collateral items, and PT. loss when the collateral is under the supervision of PT. Pegadaian (persero) Mengwi Branch. But if PT. Pegadaian (persero) Mengwi Branch is not responsible for its obligations, then it can be subject to administrative sanctions as stated in Article 60 UUPK.